The Politics of Restructuring : Trade Unions on the Defensive in Britain Since 1979 - Waddington, Jeremy; Whitston, Colin (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1994)
This paper shows that restructuring and the associated political programme have thrown British unions onto the defensive. It rejects arguments that unions have been 'tamed' and that unions are in terminal crisis, but argues that union structures and practices intended for application in the 1960s and 1970s were found to be inappropriate for the circumstances of the 1990s. Since 1979 a range of policy initiatives have been launched to address existing weaknesses. A review of these identifies several shortcomings and suggests that attempts to establish a 'new' agenda have only just begun.